Conservation biology : - Dyke, Fred Van (McGraw-Hil, 2003)
The book focuses on the preservation of worldwide biodiversity through the conservation of habitats and restoration of ecosystems. It assumes a basic knowledge of cellular, organismal, and ecosystem functions and characteristics, complemented by a basic understanding of reproductive biology, including the characteristics of DNA and its replication and mutation